Vessel wall plasticity in large vessel giant cell arteritis: an ultrasound follow-up study. (12th December 2018) - Aschwanden, Markus; Schegk, Elke; Imfeld, Stephan; Staub, Daniel; Rottenburger, Christof; Berger, Christoph T; Daikeler, Thomas
Abstract: Objectives: To assess changes of arterial vessel wall morphology in large vessel GCA patients (LV-GCA) by repeated US. Methods: Patients with LV-GCA on US examination were followed up 6, 12 and 24 months after diagnosis by US of the temporal, vertebral, carotid (common, internal, external), subclavian, axillary, femoral (deep, superficial and common) and popliteal arteries. Clinical and laboratory data were assessed at each visit. Vessel wall thickening was classified as moderate, marked or arteriosclerotic. Results: A total of 42 patients (26 female) with a median age of 75 years at diagnosis had in median 2 (range 1–3) US follow-up exams. Twenty-eight had both LV and temporal artery involvement and 14 had LV-GCA only. The common carotid, subclavian, axillary, popliteal and/or superficial femoral artery were most commonly involved. Reduction of LV wall thickening occurred in 45% of patients during follow-up, corresponding to 71 of the 284 (25%) initially 'vasculitic' LV segments. In contrast, a reduction of vessel wall thickening in the temporal artery was found in 85% of patients. Of the LVs, the vertebral, axillary, subclavian and deep femoral arteries were most likely to improve. There was no difference in relapses or the received cumulative steroid dose between patients with or without a reduction of vessel wall thickening (temporal artery or LV) during follow-up. Conclusion: Regression of wall thickening within the LV is significantly less common than in the temporal artery and irrespective of clinical remission. Morphological regression does not seem to be a useful predictor for relapses.